2010 IEEE International Reliability Physics Symposium 2010
DOI: 10.1109/irps.2010.5488688
|View full text |Cite
|
Sign up to set email alerts
|

Disconnection of NiSi shared contact and its correction using NH<inf>3</inf> soak treatment in Ti/TiN barrier metallization

Abstract: During Ti/TiN barrier metallization of a shared contact in SRAM, an NH 3 soak treatment selectively deoxidized silicon oxide on NiSi at the gate shoulder, improving the resistance of the contact. This deoxidizing NH 3 soak treatment drastically reduced the drawbacks of conventional NH 3 plasma treatment: plasma-induced damage of gate oxide and excessive nitridation of Ti/TiN. Although NH 3 gas does not kinetically deoxidize silicon oxide, it does selectively deoxidize silicon oxide on the NiSi. We think that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The specimens were the same as mentioned above. The XPS peak positions in the Si 2p spectrum reported for SiO 2 [15], [16] and Si [14] are denoted by vertical bars in the figure. It has been reported that silicide was formed after Ni sputter deposition on a cleaned Si surface without the need for annealing [17] and that the surface of silicide becomes covered with SiO 2 and not NiO by air exposure [15].…”
Section: B Blanket Wafer Analysesmentioning
confidence: 99%
“…The specimens were the same as mentioned above. The XPS peak positions in the Si 2p spectrum reported for SiO 2 [15], [16] and Si [14] are denoted by vertical bars in the figure. It has been reported that silicide was formed after Ni sputter deposition on a cleaned Si surface without the need for annealing [17] and that the surface of silicide becomes covered with SiO 2 and not NiO by air exposure [15].…”
Section: B Blanket Wafer Analysesmentioning
confidence: 99%
“…1) Metal silicides, such as titanium, cobalt, and nickel silicide, have been widely applied as electrodes in complementary metal oxide semiconductor (CMOS) field-effect transistors to enhance the channel drive current. [2][3][4] Nickel monosilicide electrodes have been fabricated in the 65-nm-node and beyond CMOS devices [5][6][7][8][9][10][11][12][13] because they are suitable for miniaturized transistors owing to the lower forming temperature and less consumption of silicon than titanium and cobalt silicides. In addition, nickel monosilicide has been incorporated with platinum (Pt) to enhance its thermal stability, viz., to prevent monosilicide from transforming into disilicide.…”
Section: Introductionmentioning
confidence: 99%